Handbook of Oncology and Immunology - Melendez, Tenesha, author 648329; Thacker, Jayson, author 648330 (Delhi, India : College Publishing House, 2012)
/ Desktop / Fulltext % 20ebooks / 180 ou may not have access to some features. View permissions Oncologist Occupation search Names Type Activity sectors Fields of employment Doctor , Medical Specialist Specialty Medicine Description Doctor of Medicine +2 Education required Medical residency Fellowship ( medicine ) Hospitals , Clinics Screening efforts A Oncology ( from the Ancient Greek onkos ( oykoç ) , meaning bulk, mass, or tumor, and the suffix -logy (-koyia), meaning "study of") is a branch of medicine that deals with tumors (cancer). A medical professional who practices oncology is an oncologist. Oncology is concerned with: the diagnosis of any cancer in a person, Therapy (e.g., surgery, chemotherapy, radiotherapy and other modalities), Follow-up of cancer patients after successful treatment, Palliative care of patients with terminal malignancies, Ethical questions surrounding cancer care, Screening efforts : of populations, or of the relatives of patients (in types of cancer that are thought to have a hereditary basis, such as breast cancer).